2018
DOI: 10.1037/amp0000371
|View full text |Cite
|
Sign up to set email alerts
|

The contributions of affective traits and emotion regulation to internalizing disorders: Current state of the literature and measurement challenges.

Abstract: Dysfunctional affective processes are central to the experience of internalizing disorders (e.g., depression, anxiety, and related disorders). Specifically, extreme positive affect and elevated negative affect each have unique and robust patterns of associations with internalizing symptoms This article examines affect as both an individual difference and a within-person dynamic process that unfolds over time. Recent research is reviewed that clarifies the hierarchical structure of affect and facet-level associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 83 publications
1
20
1
Order By: Relevance
“…Concerning anxiety, the findings supported our hypothesis that alexithymia mediates the association between negative affectivity and both state and trait anxiety while controlling for age and gender. Such findings are compatible with prior research indicating that negative affectivity is positively associated with emotion regulation strategies (Naragon-Gainey et al, 2018;Malesza, 2019) and that emotion regulation strategies can help with modulating anxiety (Craske, 2003;Lonigan and Vasey, 2009). The current study brings these facets together, demonstrating the pathway from negative affectivity to state and trait anxiety via alexithymia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Concerning anxiety, the findings supported our hypothesis that alexithymia mediates the association between negative affectivity and both state and trait anxiety while controlling for age and gender. Such findings are compatible with prior research indicating that negative affectivity is positively associated with emotion regulation strategies (Naragon-Gainey et al, 2018;Malesza, 2019) and that emotion regulation strategies can help with modulating anxiety (Craske, 2003;Lonigan and Vasey, 2009). The current study brings these facets together, demonstrating the pathway from negative affectivity to state and trait anxiety via alexithymia.…”
Section: Discussionsupporting
confidence: 91%
“…It can be defined as the proneness to experience negative emotional states, and to activate defensive motivational systems (Craske, 2003). This leads to the tendency to frequently experience negative affective states (e.g., fear, sadness, anger, and guilt), to withdraw from potentially risky situations, and to react intensely to stress (Naragon-Gainey et al, 2018). Even if there is a certain association between negative affectivity and anxiety, these two constructs are not completely overlapping.…”
Section: Affectivity Emotion Regulation and Anxietymentioning
confidence: 99%
“…A second possibility is that the constructs assessed in this study—and clinical psychology intervention research more broadly—have shown considerable overlap, both conceptually and statistically [ 74 , 75 ], and may not reflect entirely distinct constructs. Additional measurement-focused work is needed to determine the extent to which self-report assessments of agency, perceived control, hopelessness, self-hate, and numerous other “thinking styles” commonly studied in intervention research reflect genuinely distinct factors, versus features of a shared latent construct.…”
Section: Discussionmentioning
confidence: 99%
“…For example, negative beliefs about emotions and one's ability to effectively manage emotions are associated with greater use of avoidance and lower levels of psychological health (De Castella, Platow, Tamir & Gross, ; Yoon, Dang, Mertz & Rottenberg, ). Emotion regulation abilities may thus have particular relevance to understanding and treating mental health issues (Naragon‐Gainey, McMahon & Park, ). One clinically relevant and empirically supported model of emotion regulation abilities and difficulties is provided by Gratz and Roemer ().…”
Section: Introductionmentioning
confidence: 99%